How Entrepreneurship Education and Social Support Affect Students’ Entrepreneurial Intentions in Jakarta Vocational Schools: Moderation by Self-Efficacy - Larasati Indah Lestari; Dr. Rd. Tuty Sariwulan, M.Si; Dr. Siti Nurjanah, SE., M.Si (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of Entrepreneurship Education and Social Support on Entrepreneurial Intention, moderated by Self-Efficacy, among students of SMK Negeri 44 Jakarta, SMK Negeri 14 Jakarta, and SMK Negeri 31 Jakarta. The research employs a quantitative approach with data analysis using the Structural Equation Modeling (SEM) method via the SmartPLS application, involving 187 student respondents. The results show that Entrepreneurship Education has a positive and significant effect on Entrepreneurial Intention (H1), and Social Support also positively influences Entrepreneurial Intention (H2). Self-Efficacy is proven to positively moderate the relationship between Entrepreneurship Education and Entrepreneurial Intention (H3). Conversely, Self-Efficacy negatively moderates the relationship between Social Support and Entrepreneurial Intention (H4).